Cancer Risk After Midurethral Sling Surgery Using Polypropylene Mesh. Issue 6 (June 2018) - Altman, Daniel; Rogers, Rebecca G.; Yin, Li; Tamussino, Karl; Ye, Weimin; Iglesia, Cheryl B.
Abstract : (Abstracted from Obstet Gynecol 2018;131:469–474) The criterion standard surgery for stress urinary incontinence (SUI) is the midurethral sling procedure. Since its introduction in 1997, this procedure has been widely used for pelvic reconstructive surgery.